Global Pricing of Carbon‐Transition Risk - BOLTON, PATRICK; KACPERCZYK, MARCIN (Journal of Finance, 2023)
ABSTRACT The energy transition away from fossil fuels exposes companies to carbon‐transition risk. Estimating the market‐based premium associated with carbon‐transition risk in a cross section of 14,400 firms in 77 countries, we find higher stock returns associated with higher levels and growth rates of carbon emissions in all sectors and most countries. Carbon premia related to emissions growth are greater for firms located in countries with lower economic development, larger energy sectors, and less inclusive political systems. Premia related to emission levels are higher in countries with stricter domestic climate policies. The latter have increased with investor awareness about climate change risk.